A review of mortality in type 2 diabetes mellitus - Nailya Sayfullaevna Asfandiyarova (Сахарный диабет)
The morbidity and mortality associated with type 2 diabetes have increased over recent years. The causes of death include cardiovascular disease, cancer, infection, kidney disease and diabetic coma. Risk factors for death are a sedentary lifestyle, obesity, smoking, sex, age, duration and severity of diabetes, macro- and microvascular complications and hyper- and hypoglycaemic states. Adequate glycemic control and moderate exercise along with the use of antiplatelet agents (e.g. aspirin), statins, antihypertensives and metformin can reduce mortality. Intensive glucose control was associated with an increased risk of severe hypoglycaemia and death, and surgical intervention increased the risk of death.